Species diversity of Annonaceae in the four selected protected areas in the Bicol Region, Philippines - ANNE RETUERMA-DIONEDA; GRECEBIO JONATHAN D. ALEJANDRO (Biodiversitas Journal of Biological Diversity, 2023)
Abstract. Retuerma-Dioneda A, Alejandro GJD. 2023. Species diversity of Annonaceae in the four selected protected areas in the Bicol Region, Philippines. Biodiversitas 24: 5428-5438. An explorational survey of four selected protected areas (PAs) was conducted in the Bicol region for Annonaceae. The study aimed to provide species diversity of Annonaceae with an account of their endemicity and distribution. The four PAs were the Abasig-Matogdon-Mananap Natural Biotic Area (AMMNBA), Bulusan Volcano Natural Park (BVNP), Mt. Isarog Natural Park (MINP), and Mt. Mayon Volcano Natural Park (MMVNP). Thirty samples were collected and identified, 16 species belonging to 13 genera, namely Annona, Artabotrys, Cananga, Drepananthus, Goniothalamus, Fissistigma, Friesodielsia, Meiogyne, Monoon, Phaeanthus, Polyalthia, Popowia, and Uvaria. Miliuseae is the most species-rich tribe with 7 species (43.75%), followed by Uvarieae with 4 species (25%), Annoneae with 2 species, Canangeae with 2 species (12.5% each), and Xylopieae with 1 species (6.25%). A key of all Annonaceae species collected in the four PAs is provided here. Five Philippine endemic species were identified, namely G. elmeri in the four PAs; P. luzonensis in three PAs; F. lanceolata, and P. lanceolata in AMMNBA; and U. valderramensis in BVNP. AMMNBA has the highest number of species (43%). The species identified comprises 10.88% of the 147 recorded Philippine Annonaceae species. The results highlight the presence and occurrence of Annonaceae essential for management and conservation policy.